Global metabolomic profiling of tumor tissue and paired serum samples to identify biomarkers for response to neoadjuvant FOLFIRINOX treatment of human pancreatic cancer - Manoj Amrutkar; Sander Johannes Thorbjørnsen Guttorm; Anette Vefferstad Finstadsveen; Knut Jørgen Labori; Lars Eide; Helge Rootwelt; Katja Benedikte Prestø Elgstøen; Ivar P. Gladhaug; Caroline S. Verbeke (Molecular Oncology)
Neoadjuvant chemotherapy (NAT) is increasingly used for the treatment of non‐metastatic pancreatic ductal adenocarcinoma (PDAC) and is established as a standard of care for borderline resectable and locally advanced PDAC. However, full exploitation of its clinical benefits is limited by the lack of biomarkers that assess treatment response. To address this unmet need, global metabolomic profiling was performed on tumor tissue and paired serum samples from patients with treatment‐naïve (TN; n = 18) and neoadjuvant leucovorin calcium (folinic acid), fluorouracil, irinotecan hydrochloride and oxaliplatin (FOLFIRINOX)‐treated (NAT; n = 17) PDAC using liquid chromatography mass spectrometry. Differentially abundant metabolites (DAMs) in TN versus NAT groups were identified and their correlation with various clinical parameters was assessed. Metabolomics profiling identified 40 tissue and five serum DAMs in TN versus NAT PDAC. In general, DAMs associated with amino acid and nucleotide metabolism were lower in NAT compared to TN. Four DAMs—3‐hydroxybutyric acid (BHB), 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid (CMPF), glycochenodeoxycholate and citrulline—were common to both tissue and serum and showed a similar pattern of differential abundance in both groups. A strong positive correlation was observed between serum carbohydrate 19‐9 antigen (CA 19‐9) and tissue carnitines (C12, C18, C18:2) and N8‐acetylspermidine. The reduction in CA 19‐9 following NAT correlated negatively with serum deoxycholate levels, and the latter correlated positively with survival. This study revealed neoadjuvant‐chemotherapy‐induced changes in metabolic pathways in PDAC, mainly amino acid and nucleotide metabolism, and these correlated with reduced CA 19‐9 following neoadjuvant FOLFIRINOX treatment.